MANAJEMEN MUAL DAN MUNTAH PADA PASIEN KANKER PARU-PARU - Refianti Putri Kusuma Kusuma; Made Suandika; Tophan Heri Wibowo (Jurnal Cakrawala Ilmiah, 2022)
Cancer is a disease that occurs due to abnormal reproduction of cells in the body. Chemotherapy is a type of modality therapy in cancer patients which is often done in addition to surgery, radiotherapy, hormone therapy and immunotherapy. Nausea and vomiting are the most common and disturbing effects of cancer patients undergoing chemotherapy. Management of nausea and vomiting needs to be done appropriately and in accordance with the problems experienced in order to reduce the incidence of nausea and vomiting. The purpose of this study was to describe the management of nausea and vomiting in lung cancer patients. This research uses descriptive research method. The descriptive method in this study uses a literature review design (Library Study). The search strategy method to find journals using the keywords “Cancer OR Cancer AND Lung Cancer OR Lung Cancer AND Management OR Intervention OR Management OR Intervention AND Nausea and Vomiting OR Nausea OR Vomiting OR Nausea and Vomiting AND Management of Nausea and Vomiting OR Nausea and Vomiting Management AND quantitative study ". The results of the literature review are known from 7 journals, it can be concluded that 3 journals show management of nausea and vomiting in lung cancer patients using non-pharmacologic techniques in the form of acupressure or acupuncture